2018
DOI: 10.1007/s12603-017-0938-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability and Effects of a Home-Based Exercise Program Using a Gerontechnology on Physical Capacities After a Minor Injury in Community-Living Older Adults: A Pilot Study

Abstract: This twelve-week HEP intervention using the Jintronix® gerontechnology is feasible, acceptable and safe for community-living older adults who sustained a minor injury. This intervention could increase walking speed, the most important predictor of adverse events in the elderly population, and that the improvement could be maintained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…18% (n = 15) of the studies described interventions promoting physical fitness among older participants 26‐40 . The interventions were aimed at preventing falls or further decline among older people due to frailty, sarcopenia, multiple chronic conditions, or cancer by means of improving balance, strength, and physical capacity.…”
Section: Resultsmentioning
confidence: 99%
“…18% (n = 15) of the studies described interventions promoting physical fitness among older participants 26‐40 . The interventions were aimed at preventing falls or further decline among older people due to frailty, sarcopenia, multiple chronic conditions, or cancer by means of improving balance, strength, and physical capacity.…”
Section: Resultsmentioning
confidence: 99%
“…They are motivated through an enjoyable game interface that trains motor abilities but also cognitive skills. Moreover, exergames could be implemented with different levels of difficulty, allowing each senior to begin with a comfortable level and then proceed gradually to a more difficult level [16].…”
Section: Related Workmentioning
confidence: 99%
“…To summarize, advantages of exergames compared to conventional exercises are: (1) Exergames can imply simultaneous training of physical and cognitive functions (thereby being closer to daily life requirements) (Van Diest et al, 2013); (2) Users get motivated through an engaging and interactive training (Choi et al, 2017); (3) Training principles (e.g., feedback, progression, task variability) can be implemented in the exergame structure (Healy et al, 2014; Skjæret et al, 2016); (4) Exergame training can be conducted in diverse settings, e.g., at home. Recent studies have shown high acceptability of home-based exergame training for older adults after a mild injury and for elderly living in a nursing home (Valiani et al, 2017; Lauzé et al, 2018). Thus, developing an exergame for an in-home training solution might be a promising strategy to overcome some of the barriers for training attendance in older adults.…”
Section: Introductionmentioning
confidence: 99%